On Schneewind and Kant's Method in Ethics - Karl Ameriks (Ideas y Valores)
Contemporary work on Kantian ethics often ascribes to him a "constructivist" rather than a realíst methodology. In this paper I focus on J.B. Schneewind's ímpressive historical work to the effect that such a reading fits in nicely with stressing several significant similarities between Kant and modem British moralists who employed a kind of "skeptical method" in ethics. After displaying the merits of this interpretation, 1 argüe that there are nonetheless significant and defensible differences between Kant himself and his British predecessors and constructivist successors.